2015
DOI: 10.1016/j.clinthera.2015.03.027
|View full text |Cite
|
Sign up to set email alerts
|

Asthma Treatments and Mental Health Visits After a Food and Drug Administration Label Change for Leukotriene Inhibitors

Abstract: Purpose In 2009, the US Food and Drug Administration (FDA) mandated a label change for leukotriene inhibitors (LTIs) to include neuropsychiatric adverse events (eg, depression and suicidality) as a precaution. This study investigated how this label change affected the use of LTIs and other asthma controller medications, mental health visits, and suicide attempts. Methods We analyzed data (2005–2010) from 5 large health plans in the US Population-Based Effectiveness in Asthma and Lung Diseases (PEAL) Network.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 20 publications
1
20
0
1
Order By: Relevance
“…All of the 70 publications included are observational studies based on routinely collected health data, which included health insurance or hospital records. Thus, no RCTs were found for the defined search period.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All of the 70 publications included are observational studies based on routinely collected health data, which included health insurance or hospital records. Thus, no RCTs were found for the defined search period.…”
Section: Resultsmentioning
confidence: 99%
“…In 66 out of 72 studies, intended changes in drug therapy were investigated with different results regarding their effectiveness. Contents of the safety warnings were described as effective in 28 out of 72 studies . In 12 studies, the authors concluded that the content of the safety warnings investigated did not lead to a change in drug therapy .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, the 2013 YRBS did not include information on prescribed asthma medication, current asthma status, or asthma severity. Research investigating the impact of medications with leukotriene modifiers such as inhalers and steroids has been of interest since the Food and Drug Administration mandated medication labels to contain information on possible suicidality in 2009 . Other researchers have observed that parents of children with harsh asthma conditions were more troubled about their children being victims of bullying .…”
Section: Discussionmentioning
confidence: 99%
“…Research investigating the impact of medications with leukotriene modifiers such as inhalers and steroids has been of interest since the Food and Drug Administration mandated medication labels to contain information on possible suicidality in 2009. [36][37][38][39] Other researchers have observed that parents of children with harsh asthma conditions were more troubled about their children being victims of bullying. 20 Thus, the ability to include more information on the medication prescribed to control asthma symptoms, asthma symptoms at the time of the survey, and severity of asthma could provide a better understanding of the relationship among having asthma, being bullied, and exhibiting suicidal ideation and/or behaviors.…”
Section: Limitationsmentioning
confidence: 99%